Molecular Characterization of African Swine Fever Virus From 2019-2020 Outbreaks in Guangxi Province, Southern China - Shi, Kaichuang; Liu, Huixin; Yin, Yanwen; Si, Hongbin; Long, Feng; Feng, Shuping (Frontiers in Veterinary Science, 2022)
African swine fever virus (ASFV) causes contagious hemorrhagic disease of pigs with high morbidity and mortality. To identify the molecular characteristics of ASFV strains circulating in Guangxi province, southern China, a total of 336 tissue samples collected from 336 domestic pigs that died as a result of severe hemorrhagic disease during 2019-2020 were tested for ASFV. Furthermore, 66 ASFV strains were genetically characterized by sequence analysis of the C-terminal region of B646L (p72) gene, the complete E183L (p54) gene, the variable region of EP402R (CD2v) gene, the central variable region (CVR) of B602L gene, the full MGF505-2R gene, and the tandem repeat sequence (TRS) within intergenic region (IGR) between the I73R and I329L (I73R/I329L) genes. Phylogenetic analysis revealed that the ASFV strains from Guangxi province belonged to genotypes I and II based on the B646L (p72) and E183L (p54) genes, and there were eight different tetrameric TRS variants based on the CVR of B602L gene. Phylogenetic analysis of the EP402R (CD2v) gene revealed that these ASFV strains belonged to serogroups 4 and 8. Eight of the 66 strains belonged to genotype I and serogroup 4, and showed deletion of whole MGF505-2R gene. The sequence analysis of the IGR between the I73R/I329L genes showed that IGR II and III variants were co-circulating in Guangxi province. The results indicated that ASFV strains circulating in Guangxi province during 2019-2020 outbreaks showed high genetic diversity, of which genotypes I and II, as well as serogroups 4 and 8, were simultaneously circulating in Guangxi province, and there existed wild-type and naturally gene-deleted strains in the field. This is the first detailed report on the molecular characterization of the ASFV strains circulating in southern China, and serogroup 4 in China.